Negative Politeness Strategy in Sellers and Buyers Interaction at “Pasar Kamis” in Pulau Aro Village - Magria, Vera; Jasmir, Rini Afrilesa (Jurnal Ilmiah Langue and Parole, 2025)
The aims of this research is to determine  negative politeness strategies in sellers and buyers interaction at “Pasar kamis” in Pulau Aro Village. Several phases of the descriptive qualitative approach were used to perform this study. The first strategy involved gathering information by means of observation, elicitation, and advanced techniques such as record and taking notes. Yule's and levinson’s theory and a few related and corroborating literature are used to assess data. The researcher employed the referential method to analyze the data. The data analysis is then presented in an informal manner.The analysis's findings were presented in an informal method. Seven types of negative politeness strategies can be identified from the 10 form categories, including: be conventionally, indirect, question (hedge, be pessimistic, minimize the imposition, and  apologize.